The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/mmi.12805
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent effects of transcription‐ and translation‐halting drugs on the spatial distributions of the Escherichia coli chromosome and ribosomes

Abstract: Summary Previously observed effects of rifampicin and chloramphenicol indicate that transcription and translation activity strongly affect the coarse spatial organization of the bacterial cytoplasm. Single-cell, time-resolved, quantitative imaging of chromosome and ribosome spatial distributions and ribosome diffusion in live E. coli provides insight into the underlying mechanisms. Monte Carlo simulations of model DNA-ribosome mixtures support a novel nucleoid-ribosome mixing hypothesis. In normal conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
170
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(210 citation statements)
references
References 56 publications
28
170
1
1
Order By: Relevance
“…Thus, like the protein synthesis inhibitors, the initial effect of rifampicin is consistent with disruption of the expansive force associated with transertion. The expansion at longer times following rifampicin treatment may be due to indirect effects of transcription inhibition or from entropic effects of ribosomal subunits mixing with the nucleoid (6). This latter hypothesis is also consistent with single-particle-tracking studies of bound and free ribosomal subunits that detected a large percentage of free subunits co-localized with nucleoid-associated proteins (75).…”
Section: Effects Of Antibiotics On the Nucleoidsupporting
confidence: 59%
See 2 more Smart Citations
“…Thus, like the protein synthesis inhibitors, the initial effect of rifampicin is consistent with disruption of the expansive force associated with transertion. The expansion at longer times following rifampicin treatment may be due to indirect effects of transcription inhibition or from entropic effects of ribosomal subunits mixing with the nucleoid (6). This latter hypothesis is also consistent with single-particle-tracking studies of bound and free ribosomal subunits that detected a large percentage of free subunits co-localized with nucleoid-associated proteins (75).…”
Section: Effects Of Antibiotics On the Nucleoidsupporting
confidence: 59%
“…Furthermore, cells in most early studies were fixed, which could induce artifacts in nucleoid morphology. These issues were largely addressed in a recent study that followed the effects of transcription and translation inhibitors on the nucleoid in live cells and in real time using a microfluidic device (6). It was found that for late times (>20 min), translation inhibitors (chloramphenicol and kasugamycin) produced condensed nucleoids, whereas a transcription inhibitor (rifampicin) produced expanded nucleoids, consistent with earlier reports.…”
Section: Effects Of Antibiotics On the Nucleoidsupporting
confidence: 56%
See 1 more Smart Citation
“…Statistical models have suggested that this phase separation between the ribosome-containing cytoplasm and the DNA can be explained by simple entropic forces: The DNA polymer avoids the walls to maximize conformational entropy, and the polysomes (multiple 70S ribosomes on a single mRNA) occupy the empty space near the walls to maximize translational entropy (41). Although mRNA-bound 70S ribosomes are excluded from the nucleoid, it has recently been shown that free 50S and 30S subunits do have access to the nucleoid center (32,42). These results indicate that both transcription and translation can begin in the center of the nucleoid (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In E. coli, the RNA transcribed from the gsp operon has been mapped (44), and multiple translation initiation events (45) ensure that many molecules of GspD (and the other subunits of the T2SS) would be synthesized in close proximity, translocated into the periplasm in close proximity, and translocated to arrive at the same or a neighboring LolB receptor site within a short window of time (46)(47)(48)(49). Computer simulations and protein localization studies confirm that transertion creates local regions of high concentration for a given membrane protein (reviewed by Matsumoto et al [48]).…”
Section: Discussionmentioning
confidence: 99%